The role of agricultural drainage in controlling the effectiveness of two-stage ditches in Sweden - Nagarajan, Neerajaa (2021)
Increased agricultural activities are causing eutrophication in downstream water bodies. To mitigate nutrient leaching from cropland, various in-field and edge-of-field practices have been implemented. One such measure, the two-stage ditch (SD), with wider vegetated terraces than a traditional trapezoidal ditch (TD), is meant to slow down water flow, thus enabling sediments to settle and nutrients to be biogeochemically processed. The stability and nutrient removal of the SDs are being studied recently, but the influence of existing in-field drainage on the functionality of SDs, especially during high flows, has not been considered yet. It is especially important to learn the source and transport of nutrients and suspended sediments (SS) in the drains so that suitable in-field practices can be implemented. This study included collecting grab samples from all the active subsurface drains and tributaries, lab analyses for concentration (mgl-1) and loads (mgs-1) of four: ammonia-nitrogen (NH4N), nitrate-nitrogen (NO3N), orthophosphate (PO4P), total phosphorous (TP), SS and dissolved organic matter (DOM) indices. Contribution from individual drains and tributaries were estimated with an attempt to explain the source of the inputs by SS and DOM indices. The retention of the nutrients and SS in the SDs for each month and the influence of the drains and tributaries in terms of input % were also calculated. The results showed that drains in clayey soil had loads (mgs-1) accounting for 87% of PO4P (SD1) and 78% of SS (SD3) of the total input to the SD. However, in terms of concentrations (mgl-1), land use played an important role where sites with higher agricultural land use contributed with NO3N concentration up to 300% higher than (SD8) than the SD. DOM indices of drain water showed that the months following snowmelt between January and March had highly humified, aromatic compounds from terrestrial sources. The DOM stored nutrients and they were decomposable. This period saw a net nutrient/SS addition in SD downstream to an extent of -256% (SD3: January NO3N) and -387% (SD5: March SS) in several SDs, potentially due to less vegetation, high flows, decreased denitrification rates, and erosion from the banks. April and May had a change in DOM in drains with more microbial-like, low MW compounds. While the months included cropping season with fertilization and its direct effects on the drain concentration, the removal rate of SDs was high in most cases, possibly due to active terrace biota. The impact from drains and tributaries were detrimental in two situations: when high loads of nutrients and SS interfered in subsequent removal by the SD (SDs 1 and 3), when high concentrations were combined with unstable SDs that couldn’t effectively reduce the inputs (SDs: 3, 5, and 10). To avoid further leaching to downstream ecosystems, future studies should consider techniques to reduce erosion by strengthening the terraces and reduce leaching from drains by effective in-field management.